KAJIAN TEMATIS Al-QUR’AN DAN HADITS TENTANG KEPEMIMPINAN - Pramitha, Devi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Leaders and leadership are two interrelated problems of daily life in society, organization, nation and state. The development level of society, organizations and nations and countries influenced by the leaders and leadership. Islam itself as a religion rahmatan lil 'Alamin also put the issue of leaders and leadership as one of the major issues in his teaching. In the Qur'an and Hadith leadership gets a share of the discussion is not small, many verses of the Koran and the hadiths of the Prophet who Membincang about leadership. In the Islamic concept itself, leadership can be defined as a concept of interaction, relationships, processes of authority, influence activities, directs and coordinates both horizontally and vertically.Â Keywords: leadership, al-Qurâ€™an, hadith